Efeitos das transformações demográficas e da composição educacional na extensão da vida laboral e na dinâmica econômica brasileira - Anderson Rocha de Jesus Fernandes (2021)
BACKGROUND The changes in the educational attainment and the availability of social security schemes have compressed the working life cycle: people start to work late and leave the workforce early (COILE, 2018; QUEIROZ; FERREIRA, 2021). The declining number of workers in adult ages, associated with the aging process, can raise negative economic pressures and compromise the sustainability of transfer systems. OBJECTIVE This research aims to investigate the effects of the aging process on support and dependency ratios, taking into account the shifts in the educational composition and its connection to a longer working life. METHODS The methods consist of calculating dependency and support ratios to verify the relation between the demographic-educational dynamic and the economic activity. The investigation of the determinants of labor supply and income of adults and elderly was carried out using logistic and linear models, which produced inputs for simulation under the provision of scenarios related to education and technological progress. Demographic dividends could be measured considering an older workforce. RESULTS Results show an ongoing aging process which is still changing the dependency levels. There is still room for the fruition of the changing age structure (first dividend), mostly, if one considers consumption and labor income age profiles. Educational attainment is relevant to working longer. However, this also depends on the adoption of other measures, such as reductions in levels of informality and changes in the social security system. CONCLUSIONS The workforce in the future will be aged and potentially more educated. However, its size will depend on the pace of the advances in education. The silver dividend and the levels of productivity are also subjected to potential changes in economic-institutional aspects. If appropriate measures – schooling, progress in the labor market, and changes in retirement – are promptly taken, the impacts of aging could be mitigated. CONTRIBUTIONS This study contributes to the debate about the economic effects of demographic changes by investigating the relation among aging, education, and labor market in a macro-micro perspective. It could determined, through the simulation process, potential circumstances associated with an elderly labor supply in Brazil, considering the country’s deep social inequalities.